The Fish Community Of The Sario River Estuary In Manado City - Dauhan, Dulce Maria; Rondonuwu, Ari B.; Rangan, Jety K.; Lumingas, Lawrence J. L.; M.Si, Fransine B.; Lohoo, Anneke V. (Jurnal Ilmiah Platax, 2024)
The purpose of this research was to determine the fish species composition, relative abundance, and community structure, including ecological indices. The methods used in this study were general field survey methods and fish capture methods using the “swept area” method (Sparre & Venema, 1998). Data were collected based on the time of collection using beach seine gear. The research was conducted in several stages, including fish catching in the field, data analysis, and discussion. The results of this study showed that there were 13 species from 11 families of fish in the Sario River Estuary. The total population obtained in June and July was 292 individuals. 215 individuals were caught in June and 77 individuals were caught in July. The highest composition in both months was the species Ambassis urotaenia, while the lowest number was several species, namely Caranx ignobilis, Osteomugil cunnesius, and Zenarchopterus buffonis. The highest relative abundance in both months was the species Ambassis urotaenia (73.49% and 66.23%). The lowest relative abundance was Caranx ignobilis, Tylosurus crocodilus, and Zenarchopterus buffonis with values of (1.30%). Sillago sihama, Chelonodontops patoca (0.93%). The results of the study showed the community structure in Sario River Estuary in June and July (H' = 0.91 – 0,97, J' = 0.44 – 0.54, D = 0.49 -0.57). Keywords: Fish, Sario River Estuary, Relative Abundance, Community Structure Abstrak Penelitian ini bertujuan untuk mengetahui komposisi jenis ikan, kelimpahan relatif dan struktur komunitas yang meliputi indeks ekologi.Metode yang digunakan dalam penelitian ini yaitu metode umum survei lapangan dan metode penangkapan ikan menggunakan metode “swept area” (Sparre & Venema, 1998). Pengambilan data dilakukan berdasarkan waktu pengambilan menggunakan alat tangkap pukat pantai (beach seine). Penelitian ini dilakukan dengan beberapa tahapan yaitu penangkapan ikan di lapangan yang akan menjadi data, analisis data serta pembahasan.Hasil penelitian ini menunjukkan terdapat 13 spesies dari 11 famili ikan di Muara Sungai Sario. Dengan total populasi yang didapat pada bulan Juni dan sbulan Juli 292 individu. 215 individu tertangkap pada bulan Juni dan 77 individu tertangkap pada bulan Juli. Komposisi tertinggi pada kedua bulan adalah jenis Ambassis urotaenia, sedangkan jumlah terendah ada beberapa jenis yaitu Caranx ignobilis, Osteomugil cunnesius, Zenarchopterus buffonis. Kelimpahan relatif tertinggi pada kedua bulan adalah jenis Ambassis urotaenia (73,49% dan 66,23%). Sedangkan kelimpahan relatif terendah yaitu Caranx ignobilis, Tylosurus crocodilus dan Zenarchopterus buffonis dengan nilai (1,30%). Sillago sihama, Chelonodontops patoca (0,93%). Hasil penelitian menujukkan struktur komunitas di Muara Sungai Sario pada bulan Juni dan bulan Juli (H' = 0,91 – 0,97, J' = 0,44 – 0,54, D = 0,49 -0,57). Kata kunci: Ikan, Muara Sungai Sario, Kelimpahan Relative, Struktur Komunitas.